1983
DOI: 10.1111/j.1365-2125.1983.tb02160.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diet upon serum concentrations of theophylline.

Abstract: 1 Eight patients with airways obstruction were investigated to determine if dietary components had any significant effect upon serum concentrations of theophylline when taking a slow release formulation.2 A high carbohydrate, low protein diet, given for 1 week, resulted in the area under the concentration time curve for 12 h being 33.3% greater than a high protein low carbohydrate diet given under the same conditions. 3 In contrast to two previous studies no significant effect upon the elimination half-life wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The data are further evidence that the effects of the dietary protein/carbohydrate ratio on drug metabolism in humans are quite consistent and are manifest under a variety of conditions. Previously, protein intake was shown to affect drug oxidations not only in normal subjects but also in individuals subject to energy restriction (231, malnutrition (241, liver disease (25) or pulmonary disease (26,27). The present results indicate that the dietary proteinicarbohydrate ratio can also influence drug metabolism when cytochrome P-450 enzymes are partially inhibited by cimetidine.…”
Section: Hepatologysupporting
confidence: 47%
“…The data are further evidence that the effects of the dietary protein/carbohydrate ratio on drug metabolism in humans are quite consistent and are manifest under a variety of conditions. Previously, protein intake was shown to affect drug oxidations not only in normal subjects but also in individuals subject to energy restriction (231, malnutrition (241, liver disease (25) or pulmonary disease (26,27). The present results indicate that the dietary proteinicarbohydrate ratio can also influence drug metabolism when cytochrome P-450 enzymes are partially inhibited by cimetidine.…”
Section: Hepatologysupporting
confidence: 47%
“…To model high dietary theobromine intake (6 mg/kg/day), we chose a 7-day period of daily consumption of dark chocolate. Furthermore, because other dietary constituents such as protein and carbohydrate can alter methylxanthine elimination rates in man, 9,12,18 the diets of our subjects were standardized to avoid effects from such interference.…”
mentioning
confidence: 99%
“…While the influence of diet on theophylline metabolism is not well documented, recent studies in animals and man have shown that dietary protein levels may have a significant effect on the hepatic metabolism of drugs such as theophylline. As in the case of studies in the elderly population, theophylline metabolism has been reported to be decreased (Jung 1985b;Juan et al 1986) or unchanged (Thompson et al 1983;Eriksson et al 1983) in protein deficiency when compared to a normal protein diet. The decreased clearance of theophylline is consistent with in vitro findings that there is a general reduction in the activity of the microsomes in protein deficient rats (Dickerson et al 1976;Hayes et al 1978) primarily due to a reduction in the specific enzyme activity, which is reflected in the decrease in the cytochrome P-450 content and activity of the liver (Mgbodile et al 1973).…”
Section: Discussionmentioning
confidence: 90%